The Role Of Health Security In Enhancing The Efficiency Of Health Systems To Confront Health Crises And Emergencies (The Review of Diabetic Studies, 2025)
Health crisis continues to challenge the effectiveness of health systems, but there is an acute empirical gap in understanding the direct impact of the health security capacities that were previously developed on operational performance in emergencies. Although much is stated about health security and resilience of the system, very little research provides a quantitative linkage of investments in preparedness and their efficiency outcomes. Therefore, this paper aimed to quantify the association between the health security capacity and the health system efficiency, and to explain the mechanism behind this association. The explanatory sequential design was followed, which is the mixed-method design that included data from 420 health facilities spread across various regions. The quantitative phase utilized facility operational data at the facility level and the national level in terms of health security scores based on Joint External Evaluations (JEE). DEA created efficiency scores, and multivariate models evaluated the association. The qualitative step involved the semi-structured interviews and the focus group discussions that were meant to explain the quantitative results. The findings showed that there is a significant, strong positive relationship between the JEE scores and the normalized efficiency (r 0.858, p = 0.01). Facilities with a larger health security capacity had an even stronger percentage of essential services (r = 0.924) and lower days of stockout (r = -0.836). JEE score was found to be a significant positive predictor of efficiency (Coef. = 0.015, p = 0.001) even after resource availability and the governance factors were accounted for with the help of a mixed-effects model. The paper finds that effective health security capacities are conclusive determinants of health system efficacies in times of crisis.